2017
DOI: 10.1093/nar/gkx168
|View full text |Cite
|
Sign up to set email alerts
|

The primary transcriptome of Neisseria meningitidis and its interaction with the RNA chaperone Hfq

Abstract: Neisseria meningitidis is a human commensal that can also cause life-threatening meningitis and septicemia. Despite growing evidence for RNA-based regulation in meningococci, their transcriptome structure and output of regulatory small RNAs (sRNAs) are incompletely understood. Using dRNA-seq, we have mapped at single-nucleotide resolution the primary transcriptome of N. meningitidis strain 8013. Annotation of 1625 transcriptional start sites defines transcription units for most protein-coding genes but also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 128 publications
(178 reference statements)
7
74
0
Order By: Relevance
“…This suggested that NmsRs may act in concert with Hfq. Hfq-dependent repression of prpB expression was subsequently shown to be mediated by two trans-acting sRNAs, RcoF1 and RcoF2 [27]. Northern blot analysis revealed that both the single prpB and the bicistronic prpB-prpC mRNAs were up-regulated upon the deletion of hfq or a double deletion of rcoF1 and rcoF2 [28], thereby confirming the genetic link between RcoF1/2, Hfq and prp gene expression.…”
Section: Other Regulators Of Prp Gene Expressionmentioning
confidence: 74%
See 1 more Smart Citation
“…This suggested that NmsRs may act in concert with Hfq. Hfq-dependent repression of prpB expression was subsequently shown to be mediated by two trans-acting sRNAs, RcoF1 and RcoF2 [27]. Northern blot analysis revealed that both the single prpB and the bicistronic prpB-prpC mRNAs were up-regulated upon the deletion of hfq or a double deletion of rcoF1 and rcoF2 [28], thereby confirming the genetic link between RcoF1/2, Hfq and prp gene expression.…”
Section: Other Regulators Of Prp Gene Expressionmentioning
confidence: 74%
“…Northern blot analysis revealed that both the single prpB and the bicistronic prpB-prpC mRNAs were up-regulated upon the deletion of hfq or a double deletion of rcoF1 and rcoF2 [28], thereby confirming the genetic link between RcoF1/2, Hfq and prp gene expression. By regulating prpB, RcoF1 and RcoF2 appear to be the first trans-acting sRNAs with a direct host-associated function in N. meningitidis [27].…”
Section: Other Regulators Of Prp Gene Expressionmentioning
confidence: 99%
“…RNA-seq has also had a major impact on the discovery and characterization of prokaryotic regulatory RNAs (Barquist & Vogel, 2015;Hor et al, 2018). For example, RNA-seq has been used to identify RNA ligands associated with the Hfq RNA chaperone in Salmonella enterica (Chao, Papenfort, Reinhardt, Sharma, & Vogel, 2012;Sittka et al, 2008), Neisseria meningitidis (Heidrich et al, 2017), Sinorhizobium meliloti (Torres-Quesada et al, 2014), and Escherichia coli (Bilusic, Popitsch, Rescheneder, Schroeder, & Lybecker, 2014). Homologs of hfq are present in approximately 50% of all sequenced bacterial genomes (Sun, Zhulin, & Wartell, 2002) and typically Hfq plays a major role in posttranscriptional gene regulation in these species.…”
Section: Discovery Of Small Regulatory Rnas Using Differential Rna-seqmentioning
confidence: 99%
“…Recently, we reappraised the meningococcal Hfq regulon, showing direct or indirect regulation of a large variety of cellular processes, including OMPs, the methyl citrate and TCA cycles, iron and zinc homeostasis and the assembly of ribosomal proteins . In another recent study, co‐immunoprecipitation combined with RNA sequencing of a FLAG‐tagged Hfq revealed an unexpectedly large Hfq‐RNA interactome, identifying 23 sRNA and 401 mRNA candidate targets .…”
Section: Resultsmentioning
confidence: 99%